Genetic and Clinical Features of Shwachman-Diamond Syndrome in Russian Population: Prospective Study - Maria G. Ipatova; Ekaterina A. Deordieva; Oksana A. Shvets; Anna A. Mukhina; Anna A. Moiseeva; Yulya A. Rodina; Petr V. Shumilov; Anna V. Pavlova; Elena V. Raikina; Aliy Yu. Asanov; Maria M. Litvinova; Anna Y. Shcherbina (Вопросы современной педиатрии)
Background. Shwachman-Diamond syndrome (SDS) is the rare genetic autosomal recessive disorder with pathogenic variants in SBDS gene. The spectrum of SBDS gene variants in patients with SDS and features of disease course have not been studied before in Russian population.Objective. The aim of the study was to describe all the variants of SBDS gene and clinical and laboratory abnormalities in children with SDS. Methods. In this prospective study exocrine pancreatic function was estimated by amylase and lipase activity in blood, steatorrhea presence and stool elastase levels during the initial hospitalization. Haematological disorders were analysed by complete blood count. Bone abnormalities were diagnosed via X-ray imaging. Growth delay was established due to anthropometry indicators and percentile curves. Molecular genetic testing was performed with using next generation sequencing and Senger sequencing.Results. Pathogenic variants in SBDS gene (8 in general) were revealed in 25 (89%) out of 28 children with SDS. The most common variant (in 23 patients, 82%) was с.258+2T>C, and in 18 cases it was in compound heterozygous state with c.183_184delTAinsCT. Two patients had с.653G>A (p.Arg218Gln) variant and for one patient for every of the following variants: c.258+1G>A, c.107delT, с.356G>A, c.297_300delAAGA, c.338C>T. All children with SDS had growth delay, in 11 (39%) cases we revealed bone abnormalities. In blood samples of 24 (86%) children we revealed neutropenia and less frequently anemia and thrombocytopenia. The stool elastase I decreased activity (< 200 pg/g) was revealed in 26 (92%) patients. 21 (75%) children had cytolysis syndrome.Conclusion. Pathogenic variants of SBDS gene were revealed in majority of Russian children with SDS. The most frequent are c.258+2T>C and c.183_184delTAinsCT variants. Clinical signs of Shwachman-Diamond syndrome manifest since birth with growth delay, steatorrhea and haematological disorders.